Patient Perspectives on Acquiring Spectacles: A Cambodian Experience. Issue 5 (September 2016) - Ormsby, Gail Melva; Grant-Skiba, Dawn; Naidoo, Kovin; Keeffe, Jill E.
Abstract : Purpose: To assess the perspectives of patients who acquired spectacles from an eye unit/vision center in Cambodia. Design: A sample (n = 62) of patients was selected across 4 provinces: Prey Veng, Siem Reap, Battambang, and Takeo. Methods: The Patient Spectacle Satisfaction Survey covering demographic and semistructured questions regarding patient satisfaction, style, and costs incurred was used to collect data. Information was transcribed and translated into English and analyzed by thematic coding using NVivo. Results: Although there were more women seeking eye health care treatment, there was no significant age difference. Patient satisfaction levels were high although the patients had to pay for transportation, registration, and the glasses themselves. A total of 60 patients (96.7%) stated they would recommend the refractive service center to others. Despite a high level of awareness of eye disease such as cataract, only 2 in 10 people could accurately identify cataract as a major cause of poor vision or blindness. Most of the people (52%) blamed bad vision or blindness on dust or other foreign objects getting into the eye, old age (31%), or poor hygiene (16%). Conclusions: Most people will pay eye care costs once barriers to seeking treatment have been broken via education and encouragement. Satisfaction of wearing spectacles was associated with improved vision; style, color, and fit of the spectacles; and protection from sunlight and dust. The proximity of and easy access to health facilities influenced patient desire to seek treatment.